EDUKASI NUTRISI DAN PELATIHAN PENGOLAHAN RUMPUT LAUT MENJADI MIE RUMPUT LAUT BAGI KELOMPOK WANITA PESISIR DESA KANAPA-NAPA BUTON TENGAH - Nurdin, Iin Nurdiyanty; Anwar, Lely Okmawaty; Dustan, Dustan (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Seaweed is a fishery product with great potential in Central Buton Regency, particularly in Kanapa-Napa Village, where it is the village's leading product. Currently, seaweed is sold only in dried form. However, with adequate knowledge and skills in seaweed product diversification, supported by proper management and marketing, the potential for improved food security and economic resilience can be realized, contributing to the welfare of fishing families. This community service program aims to educate the community on the nutritional benefits and economic potential of seaweed if processed into value-added food products. The program further guides the community in producing seaweed-based products, specifically seaweed noodles, and provides training on packaging and digital marketing. The methods used in this program include educational outreach and hands-on training with a participatory partner approach, beginning with initial preparations such as a direct field survey and partner needs assessment through interviews with partner groups, as well as coordination with the village government and the service team. Following this, tools and materials were prepared. Educational sessions on the nutritional benefits and economic potential of seaweed were conducted, followed by practical training in seaweed noodle production, packaging, and labeling. Digital marketing training was then provided. This community service program successfully enhanced the community’s understanding of seaweed as a nutritious and economically valuable food resource. Through training phases covering socialization, processing practices, product branding, and online marketing, the community gained knowledge and skills in processing seaweed into high-quality, ready-to-consume products with added value. This initiative is expected to create sustainable new economic opportunities, strengthen local food security, and improve the welfare of Kanapa-Napa Village residents